IMPACT OF DIFFERENT REARING SYSTEMS AND AGE ON BOVANS WHITE LAYER'S PERFORMANCE, EGG QUALITY TRAITS AND SYNTHESIS OF HEAT SHOCK PROTEIN 70 kDa - Baykalir, Yasin; Simsek, Ulku Gulcihan (Walter de Gruyter Gmbh, 2018)
This study was conducted to investigate the performance of laying hens and to determine possible age-related changes on external and internal quality traits of their eggs and synthesis of heat shock protein 70 kDa (HSP70) in the conventional cage and organic rearing systems. For this purpose, 4 different Bovans White hybrid flocks of the same age were monitored in each of these two systems for 52 weeks. While a total of 360 coos were examined to determine the effects of rearing system and age (30 and 60 weeks) on egg quality traits, 48 liver tissue samples were examined for the analysis of HSP70. Egg production (hen-day) and dirty egg ratio were higher in the organic rearing system (P<0.05). The age at 50% yield, the age at peak of lay, and peak production rate were calculated as 156, 218.75 days and 95.98% in the conventional system, and 155.75, 201.50 days, and 96.56% in the organic system, respectively (P>0.05). While egg weight, albumen weight, yolk weight, shell weight, shape index, and yolk colour were higher in the organic system, the crude ash ratio of eggshell and shell ratio were higher in the conventional system (P<0.05). It was also found that the egg weight, albumen weight, yolk weight, shell weight, and the percentage of yolk were higher at 60 weeks of age (P<0.001). The percentage of shell and albumen, shape index, and yolk colour were higher at 30 weeks of age (P<0.001). The interactions between rearing system and age were statistically significant in terms of shell thickness, shape index, crude ash ratio, and yolk colour (P<0.001). Stress protein (HSP70) level was affected only by the rearing system and was higher in the organic stem (P<0.001). As a result, the organic system can be considered as advantageous in terms of egg production and quality traits and the eggs of young hens exhibited better properties. The high level of HSP70 in the organic system could indicate that hens were affected by the environmental conditions at higher rates and/or the hens reared in the organic system had a stronger antioxidant defence system.
Keywords: egg quality; HSP70; laying hens; performance; rearing systems